COMPARATIVE STUDY OF POROSITY DETERMINATION METHODS FOR OGIP IN FRACTURED BASEMENT RESERVOIR - Usman Pasarai Pasarai (Scientific Contributions Oil and Gas, 2014)
Determination of porosity in fractured basement reservoirs has always been a challenge due to thecomplexity of processes involved in the generating of pore structure as well as the rock heterogeneity. As aresult, estimate of original gas in place (OGIP) is subject to substantial uncertainty. Intention of this studyis to evaluate the most effective method to determine fracture porosity and hence reducing uncertainty ofOGIP volume in the fractured basement reservoir. The evaluation is based on comparison to the core derivedporosity as the point of reference. Included in this evaluation are the techniques of secondary porosity index(SPI), dipole share imager (DSI), dual laterolog (DL), and formation micro imager (FMI). The SPI andDSI logs derived fracture porosities are found over optimistic to the core reference. The FMI determinedfracture porosities are considered in fair agreement with core data. Results from the DL technique comparevery favorably with core data and thought to be the best calculation of porosity in the fractured basementgas reservoir investigated in this study. Those results supported by data that have been collected from thepublished literatures. Found that typical value of fracture porosities in the fractured basement rocks isless than 1%. The comparative study presented here helps in reducing uncertainty related to the fracturedbasement reservoir development.